Triceps Surae Muscle-Tendon Properties as Determinants of the Metabolic Cost in Trained Long-Distance Runners - Machado, Esthevan; Lanferdini, Fábio Juner; da Silva, Edson Soares; Geremia, Jeam Marcel; Sonda, Francesca Chaida; Fletcher, Jared R.; Vaz, Marco Aurélio; Peyré-Tartaruga, Leonardo Alexandre (Frontiers in Physiology, 2022)
Purpose: This study aimed to determine whether triceps surae’s muscle architecture and Achilles tendon parameters are related to running metabolic cost (C) in trained long-distance runners. Methods: Seventeen trained male recreational long-distance runners (mean age = 34 years) participated in this study. C was measured during submaximal steady-state running (5 min) at 12 and 16 km h–1 on a treadmill. Ultrasound was used to determine the gastrocnemius medialis (GM), gastrocnemius lateralis (GL), and soleus (SO) muscle architecture, including fascicle length (FL) and pennation angle (PA), and the Achilles tendon cross-sectional area (CSA), resting length and elongation as a function of plantar flexion torque during maximal voluntary plantar flexion. Achilles tendon mechanical (force, elongation, and stiffness) and material (stress, strain, and Young’s modulus) properties were determined. Stepwise multiple linear regressions were used to determine the relationship between independent variables (tendon resting length, CSA, force, elongation, stiffness, stress, strain, Young’s modulus, and FL and PA of triceps surae muscles) and C (J kg–1m–1) at 12 and 16 km h–1. Results: SO PA and Achilles tendon CSA were negatively associated with C (r2 = 0.69; p < 0.001) at 12 km h–1, whereas SO PA was negatively and Achilles tendon stress was positively associated with C (r2 = 0.63; p = 0.001) at 16 km h–1, respectively. Our results presented a small power, and the multiple linear regression’s cause-effect relation was limited due to the low sample size. Conclusion: For a given muscle length, greater SO PA, probably related to short muscle fibers and to a large physiological cross-sectional area, may be beneficial to C. Larger Achilles tendon CSA may determine a better force distribution per tendon area, thereby reducing tendon stress and C at submaximal speeds (12 and 16 km h–1). Furthermore, Achilles tendon morphological and mechanical properties (CSA, stress, and Young’s modulus) and triceps surae muscle architecture (GM PA, GM FL, SO PA, and SO FL) presented large correlations with C.